Autoantibodies in the Diagnosis, Monitoring, and Treatment of Membranous Nephropathy - Tesar, Vladimir; Hruskova, Zdenka (Frontiers in Immunology, 2021)
Discovery of anti-podocyte antibodies in primary membranous nephropathy revolutionized our approach to the diagnosis and treatment of this disease. Evaluation of serum levels of anti-podocyte antibodies opened the possibility of non-invasive diagnosis of primary membranous nephropathy and helps to distinguish between primary and secondary membranous nephropathy although the relation between anti-podocyte antibodies and cancer remains to be better elucidated. Serum levels of anti-PLA2R antibodies directed against the major podocyte autoantigen are related to the activity of the disease and the decrease of serum levels of anti-PLA2R in response to treatment (immunologic remission) also serves as an early indicator of the later putative proteinuric remission enabling to personalize the treatment. Serum levels of anti-PLA2R antibodies predict renal outcome in terms of both the remission and the risk of progression to the end-stage renal disease. Positive anti-PLA2R antibodies before renal transplantation are associated with the risk of recurrence of membranous nephropathy. It remains to be established if all these relations observed in patients with anti-PLA2R antibodies are also valid for antibodies directed against recently discovered minor antigens (THSD7A, NELL-1, sempahorin-3B).